Copper-doped mesoporous polydopamine nanoparticles and preparation method and application thereof

By using raw materials such as dopamine hydrochloride and copper salt, combined with P-123 and cyclohexane templates, copper-doped mesoporous polydopamine nanoparticles were prepared, which solved the problems of single mode contrast and high preparation costs of existing probes, and realized the functions of ultra-high field T1-T2 dual-mode magnetic resonance imaging and photothermal-chemical dynamic collaborative treatment.

CN118384273BActive Publication Date: 2025-03-21SUN YAT SEN UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410486285.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2025-03-21
Estimated Expiration
2044-04-22

AI Technical Summary

Technical Problem

The existing probes prepared based on Cu+ are single modal contrast agents, and the preparation process is complex and costly, so they cannot simultaneously possess ultra-high field T1-T2 dual modal contrast capability and photothermal-chemical dynamic collaborative treatment functions.

Method used

Dopamine hydrochloride and copper salts are used as basic raw materials, and P-123 and cyclohexane are templates to obtain copper-doped mesoporous polydopamine nanoparticles through specific preparation steps, which have responsive changes in T1-T2 magnetic resonance imaging capabilities and photothermal-chemical dynamic collaborative treatment functions.

Benefits of technology

It realizes ultra-high field T1-T2 dual-mode magnetic resonance imaging capabilities, has the function of photothermal-chemical dynamics collaborative treatment, can monitor the tumor chemodynamic treatment process through MRI signals, and realizes photothermal conversion under near-infrared light irradiation, promotes chemodynamic treatment, and significantly improves the treatment effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118384273B_ABST
    Figure CN118384273B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of biomedical materials, and specifically relates to a copper-doped mesoporous polydopamine nanoparticle and a preparation method and application thereof. 2+ The copper-doped mesoporous polydopamine nanoparticles (CMs) were prepared by using P‑123 and cyclohexane as the basic raw materials, and tumor cell membranes were further wrapped on the surface to construct multifunctional nano-diagnostic and therapeutic agents CMMs. The obtained CMMs can specifically recognize tumors and realize Cu in the tumor microenvironment. 2+ / Cu + It can efficiently convert GSH and produce a large amount of ·OH, and has ultra-high field T1-T2 dual-mode magnetic resonance imaging capability, which can accurately detect the chemodynamic treatment process of tumors through MRI signals; it shows good photothermal conversion ability under near-infrared light (NIR) irradiation, and can realize photothermal-promoted chemodynamic combined cancer treatment, providing a new reference for T1-T2 dual-mode MRI precise imaging visualization and combined treatment of tumors and other diseases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials, and more specifically, relates to a copper-doped mesoporous polydopamine nanoparticle and a preparation method and application thereof. Background Art

[0002] Cancer (malignant tumor) is one of the major threats to human health. With the rapid development of science and technology, new tumor diagnosis and treatment methods continue to emerge, such as photothermal therapy (PTT), chemodynamic therapy (CDT) and molecular targeted therapy. Emerging treatment methods have been continuously studied and gradually entered clinical trials, providing a broader space and richer ideas for the development of tumor treatment. In addition, the diagnosis and treatment technology that combines tumor diagnosis and treatment has received widespread attention in tumor treatment. It can realize real-time monitoring of the treatment effect, and then adjust the dosage or treatment plan in time, so as to achieve individualized drug administration for patients and improve the treatment effect. Nano drugs have attracted widespread attention in the field of tumor treatment due to their multifunctionality and multi-therapy combination, while medical imaging technology can realize the screening, monitoring and treatment of tumors due to its real-time and non-invasive advantages. Therefore, the development of new nano-diagnosis and treatment integrated probes for imaging-guided cancer combined treatment can achieve accurate detection and efficient treatment of cancer.

[0003] Medical imaging technology plays an indispensable role in the diagnosis, treatment and prognosis of cancer. Among them, magnetic resonance imaging (MRI) has attracted widespread attention due to its advantages such as high temporal and spatial resolution, no penetration depth limitation and no radiation damage. Among them, T1 is called longitudinal relaxation time, and T1-weighted imaging is mostly used to observe fat tissue or anatomical structure; T2 is called transverse relaxation time, and T2-weighted imaging is generally used to identify diseased tissue. Magnetic resonance contrast agents can further enhance MRI signals by reducing T1 or T2 of water protons. In a magnetic resonance examination, simultaneous acquisition of T1 and T2-weighted images can better display the structural information of local lesions and the observed site, and cross-validation can be used to obtain more accurate diagnostic results. Specifically, T1-T2 dual-modality MRI can be used for accurate imaging of early tumors, vascular systems, central nervous systems and other parts, avoiding the influence of MRI artifacts on diagnostic results under single modality. At present, an important development trend of MRI is to develop towards higher magnetic fields (>3.0T). The use of higher magnetic fields can give images with better signal-to-noise ratio and higher spatial / temporal resolution. Ultra-high field MRI has shown great application prospects. Therefore, constructing a multifunctional nano-diagnostic and therapeutic agent with ultra-high field T1-T2 dual-modal imaging capabilities is of great significance for the imaging visualization treatment of cancer.

[0004] Copper is a transition metal. 2+ ) has unpaired electrons in its outermost orbital and can be used as a potential contrast agent for magnetic resonance imaging. In addition, researchers have found that Cu + Plasma has significant Fenton / Fenton-like catalytic activity and can achieve chemical dynamics treatment. 2+ , Cu + The chemical kinetics of Cu-mediated catalytic reactions are very attractive. + The catalytic rate is Fe 2+ 130 times that of Cu 2+ / Cu + The conversion process can consume a large amount of GSH that is highly expressed in the tumor microenvironment, indirectly increasing the generation of highly toxic ·OH, thereby improving the therapeutic effect. 2+ The probe prepared by the complex is generally only used as a T2 contrast agent, and it is easy to confuse with the signal generated by the tissue, and there is also a disadvantage of a relatively complicated preparation process (Tian Q, Hu J, Zhu Y, et al. Sub-10nmFe3O4@Cu2-xS Core-Shell Nanoparticles for Dual-Modal Imaging and Photothermal Therapy [J]. Journal of the American Chemical Society, 2013, 135 (23): 8571-8577.). Chinese patent application CN115944728A discloses a multifunctional composite nanoenzyme material for synergistic tumor therapy, which is constructed by solid copper-doped polydopamine (Cu PDA) loaded with gold platinum nanoparticles (AuPt NPs), exhibiting catalytic activity and photothermal conversion ability and photothermal stability of peroxidase, catalase and oxidase, and can realize imaging-guided photothermal therapy, and further improve its enzyme-like activity to achieve synergistic therapy of the two. However, the preparation of this composite nanozyme material involves many synthesis steps, requires doping with gold and platinum metals, has complex reactions, high preparation costs, and cannot confirm whether it has T1-T2 dual-modality imaging capabilities. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the existing Cu-based + The prepared probe is a single-mode contrast agent, and has the defects and shortcomings of a complex preparation process and high cost. The primary purpose of the present invention is to provide a method for preparing copper-doped mesoporous polydopamine nanoparticles.

[0006] A secondary purpose of the present invention is to provide copper-doped mesoporous polydopamine nanoparticles prepared by the preparation method, and the obtained copper-doped mesoporous polydopamine nanoparticles have responsive T1-T2 magnetic resonance imaging capabilities and photothermal-chemodynamic synergistic treatment functions.

[0007] Another object of the present invention is to provide a multifunctional mesoporous polydopamine nano-therapeutic agent, which has responsive T1-T2 magnetic resonance imaging capability, homologous tumor targeting capability and photothermal-chemodynamic synergistic treatment function.

[0008] Another object of the present invention is to provide a method for preparing a mesoporous polydopamine nano-diagnostic and therapeutic agent.

[0009] Another object of the present invention is to provide the use of the copper-doped mesoporous polydopamine nanoparticles or the multifunctional mesoporous polydopamine-based nano-diagnostic and therapeutic agent in the preparation of any one or more combinations of magnetic resonance imaging contrast agents, photothermal therapy agents, and chemodynamic therapy agents.

[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0011] The present invention provides a method for preparing copper-doped mesoporous polydopamine nanoparticles, comprising the following steps:

[0012] S1. Add dopamine hydrochloride to a mixed solution of ethanol and water, add a copper salt solution, adjust the pH of the solution to 4-5, continue stirring in the dark, and react completely to obtain a copper chelated dopamine solution;

[0013] S2, adding P-123 and cyclohexane to the copper-chelated dopamine solution obtained in step S1, adjusting the solution pH to 9-11 after fully dispersing, continuously stirring in the dark, fully reacting, and post-treating to obtain copper-doped mesoporous polydopamine nanoparticles;

[0014] The mixing ratio of dopamine hydrochloride, P-123 and cyclohexane is 1 mg: (3-5) mg: (16-24) μL. Too much cyclohexane or too little P-123 will make the pore size of the mesoporous polydopamine too large or even not spherical; too little cyclohexane will make the pore size smaller or even produce a lot of non-porous polydopamine.

[0015] The present invention uses polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P-123) and cyclohexane as templates to prepare copper-doped mesoporous polydopamine nanoparticles Cu-MPDA (CMs) with uniform size and complete structure, which alleviates the problems of large aggregates or disappearance of pore size in the preparation process of traditional metal-doped polydopamine. Compared with metal-doped polydopamine with a solid structure, the copper-doped mesoporous polydopamine obtained by the present invention has a rich mesoporous structure, and its mesoporous structure increases the specific surface area. The larger specific surface area can not only accelerate the Cu + The mediated Fenton reaction rate also enhances the interaction between copper ions and surrounding water protons, significantly improving the sensitivity of MRI in detecting lesions.

[0016] Preferably, the copper salt is selected from one or more of copper sulfate, copper chloride and copper nitrate.

[0017] More preferably, the copper salt is selected from copper sulfate.

[0018] Preferably, the mass ratio of the copper salt to dopamine hydrochloride is 1:(10-12).

[0019] Furthermore, the sufficient dispersion is ultrasonic dispersion.

[0020] Furthermore, the post-treatment includes centrifugation and washing. Specifically, the fully reacted solution is centrifuged, the supernatant is removed, and the resulting precipitate is redissolved in water or ethanol. The above washing operation is repeated multiple times to remove the template and unreacted raw materials, and the product after washing is the mesoporous polydopamine nanoparticles Cu-MPDA (CMs) doped with copper ions.

[0021] Specifically, in the post-treatment, the centrifugal parameters are 10000-13000 rpm, 15-30 min; the washing is ethanol washing 2-5 times, and water washing 2-5 times.

[0022] Further, the stirring speed in step S1 and step S2 is 150-300 rpm;

[0023] Preferably, in step S1, the time required for the reaction to be complete is 8 to 12 hours.

[0024] Preferably, in step S2, the sufficient reaction time is 6 to 8 hours.

[0025] The invention also protects a copper-doped mesoporous polydopamine nanoparticle, which is prepared by the preparation method.

[0026] Preferably, the copper doping amount in the copper-doped mesoporous polydopamine nanoparticles is 8-10 wt %.

[0027] The present invention also protects a multifunctional mesoporous polydopamine nano-diagnostic agent, comprising the copper-doped mesoporous polydopamine nano-particles and a tumor cell membrane wrapped on the surface of the mesoporous polydopamine nano-particles.

[0028] The present invention further wraps tumor cell membrane on the surface of CMs to construct a multifunctional mesoporous polydopamine diagnostic and therapeutic agent (CMMs). The obtained nano-diagnostic and therapeutic agent has ultra-high field T1-T2 dual-mode magnetic resonance imaging capability, and can specifically identify tumors through the homologous targeting ability of tumor cell membranes, effectively respond to the acidic conditions of the tumor microenvironment, and can achieve Cu in the tumor microenvironment. 2+ / Cu + The efficient conversion of ·OH can be achieved, and the chemodynamic therapy process can be accurately detected by MRI. In addition, photothermal therapy can be achieved under NIR irradiation to inhibit cell activity. In addition, local heating can further promote the + The mediated chemodynamic therapy leads to the generation of a large amount of highly active and highly toxic ·OH, showing a significant photothermal-chemodynamic combined therapeutic effect.

[0029] Preferably, the tumor cell membrane is selected from one or more of breast cancer cell membrane, cervical cancer cell membrane and liver cancer cell membrane.

[0030] Furthermore, the breast cancer cell membrane is a 4T1 cell membrane, an MDA-MB-231 cell membrane or an MCF-7 cell membrane.

[0031] Preferably, the breast cancer cell membrane is a 4T1 cell membrane.

[0032] The present invention also protects a method for preparing the multifunctional mesoporous polydopamine nano-diagnostic and therapeutic agent, comprising the following steps: fully mixing the tumor cell membrane with the copper-doped mesoporous polydopamine nanoparticles, and then repeatedly extruding the copper-doped mesoporous polydopamine nanoparticles and the tumor cell membrane to obtain the agent.

[0033] Furthermore, the repeated extrusion is repeated extrusion using a liposome extruder, and the number of repeated extrusion is preferably 15 to 30 times.

[0034] Furthermore, the method for preparing the tumor cell membrane comprises the following steps: digesting the cultured tumor cells with trypsin, dispersing them in a phosphate buffered saline (PBS), repeatedly freezing and thawing them at -15 to 20°C to rupture them, and collecting the supernatant by centrifugation to obtain the tumor cell membrane.

[0035] Specifically, in the above-mentioned method for preparing tumor cell membrane, the number of repeated freezing and thawing is 3 to 5 times, the centrifugation parameters are 2000 to 5000 rpm, 10 to 15 min, 4 to 8°C; the ice water bath ultrasound parameters are: ultrasound interval is 2 to 5 s, amplitude is 10% to 20%, and ultrasound time is 1 to 5 min;

[0036] The present invention also protects the use of the copper-doped mesoporous polydopamine nanoparticles or the multifunctional mesoporous polydopamine nanodiagnostic and therapeutic agent in the preparation of any one or more combinations of magnetic resonance imaging contrast agents, photothermal therapeutic agents, and chemodynamic therapeutic agents.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention uses P-123 and cyclohexane as templates to prepare copper-doped mesoporous polydopamine nanoparticles (CMs) with more uniform size and more complete structure, thereby alleviating the problems of large aggregates or disappearance of pore size that are easily generated during the preparation of traditional metal-doped mesoporous polydopamine.

[0039] (2) The present invention utilizes the coordination effect between the catechol group of polydopamine and metal ions to form Cu 2+ Efficient chelation with MPDA enhances Cu 2+ The relaxation properties of CMMs make them show a better performance than those of reported copper-based materials (r1 = 1.791 mM at 3.0 T magnetic field strength). -1 s -1 ) Better magnetic resonance imaging effect (Wang Z, Fu L, Zhu Y, et al. Chemodynamic / photothermal synergistic therapy based on Ce-doped Cu-Al layered doublehydroxides[J]. Journal of Materials Chemistry B, 2021, 9(3): 710-718.). The longitudinal relaxation rate (r1) and transverse relaxation rate (r2) of the CMMs obtained in the present invention in a 3T magnetic resonance system are 9.53 mM respectively. -1 s -1 and 6.81mM -1 s -1 ; The longitudinal relaxation rate (r1) and transverse relaxation rate (r2) in the 7T magnetic resonance system are 1.017mM -1 s -1 and 20.572mM - 1 s -1 .

[0040] (3) The present invention constructs multifunctional nano-diagnostic and therapeutic agents CMMs. The obtained CMMs can actively target the same tumor cells through the tumor cell membrane, effectively respond to the acidic conditions of the tumor microenvironment, efficiently produce OH, and can also achieve photothermal therapy under NIR irradiation to inhibit cell activity. In addition, local heating can further promote Cu+ The mediated chemodynamic therapy leads to the generation of a large amount of highly active and highly toxic ·OH, showing a significant photothermal-chemodynamic combined therapeutic effect, providing a new idea for imaging-guided combined tumor therapy. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 These are appearance diagrams of the mixed solution changes during the CMMs preparation process of Example 1, wherein A is the appearance diagram of the clear and transparent copper-chelated dopamine solution obtained in step S1, B is the appearance diagram of the solution after cyclohexane is added and dispersed evenly in step S2, and C is the appearance diagram of the CMMs finally obtained in step S4.

[0042] Figure 2 Transmission electron micrographs of CMs prepared using TMB and F127 as templates at different locations (A-B).

[0043] Figure 3 It is a transmission electron micrograph of the premature polymerization of dopamine hydrochloride after mixing with copper ions in Comparative Example 2 (A); and a transmission electron micrograph of the premature polymerization of dopamine to form polydopamine aggregates without mesoporous morphology (B).

[0044] Figure 4 Transmission electron microscopy images of CMs (A) and CMMs (B) prepared in Example 1.

[0045] Figure 5 This is the particle size distribution diagram of CMMs nanoparticles.

[0046] Figure 6 XPS spectra of CMs (A) and fitting diagrams of C, N, O, and Cu elements (B).

[0047] Figure 7 The data statistics of the temperature rise curves of CMMs solutions with different concentrations (A) and different laser powers (B) under near-infrared laser irradiation; the data statistics of the temperature change curve of CMMs solution over time under near-infrared laser irradiation (C); and the photothermal effect diagram of CMMs solution under near-infrared laser irradiation (D).

[0048] Figure 8 Magnetic resonance images (A) and relaxation rate statistics (BC) of CMMs under different conditions at a field strength of 3.0T.

[0049] Fig. 9 Magnetic resonance images (A) and relaxation rate statistics (BC) of CMMs under different conditions at a field strength of 7.0T.

[0050] Fig.10 UV-visible spectra of MB solutions treated under different conditions (A) and at different time points (B).

[0051] Fig.11 The data statistics of cell survival rate after incubation of HUVEC cells with different concentrations of CMMs for 24h and 48h.

[0052] Fig.12 The data statistics of cell survival rate of 4T1 cells after incubation with different concentrations of CMs and CMMs for 24 hours with or without laser irradiation.

[0053] Fig.13 The data of cell survival rate after laser irradiation was statistically analyzed when different cells were incubated with different concentrations of CMMs. DETAILED DESCRIPTION

[0054] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0055] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0056] Example 1 Preparation of a tumor microenvironment responsive mesoporous polydopamine nanodiagnostic agent

[0057] A method for preparing a tumor microenvironment responsive mesoporous polydopamine nanodiagnostic and therapeutic agent comprises the following steps:

[0058] S1. Weigh 10 mg of dopamine hydrochloride and dissolve it in a mixed solution of 5 mL of deionized water and 6 mL of anhydrous ethanol. Then slowly drop 1 mL of 1 mg / mL hydrated copper sulfate solution into the solution, and adjust the pH to 5. After stirring at 200 rpm for 8 h, a clear and transparent copper-chelated dopamine solution (such as Figure 1 ).

[0059] S2, add 200 μL cyclohexane and 40 mg polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P-123) to the copper chelated dopamine solution obtained in step S1, and vigorously sonicate to evenly disperse the cyclohexane (in the form of a milky white emulsion, such as Figure 1 After that, the pH of the solution was adjusted to 9, and the reaction was stirred at 200 rpm for 6 h.

[0060] S3, centrifuge the obtained solution (13000rpm, 15min), remove the supernatant, then redissolve the precipitate in deionized water or anhydrous ethanol, centrifuge (13000rpm, 15min) and wash, and the black product obtained after washing is the copper-doped mesoporous polydopamine nanoparticles Cu-MPDA (CMs).

[0061] S4. The cultured 4T1 cells were digested with trypsin, dispersed in 1 mL PBS, and frozen and thawed three times at -20°C. The supernatant was collected by centrifugation to obtain 4T1 cell membranes. The 4T1 cell membranes were then mixed with CMs, ultrasonicated in an ice water bath for 2 min (ultrasonication interval of 2 s, amplitude of 10%), and then the CMs and 4T1 cell membranes were repeatedly extruded 20 times using a liposome extruder to finally obtain multifunctional mesoporous polydopamine nanodiagnostic agents CMMs (such as Figure 1 as shown in C in the figure).

[0062] Example 2 Preparation of a tumor microenvironment responsive mesoporous polydopamine nanodiagnostic agent

[0063] The difference between Example 2 and Example 1 is that the P-123 weighed in step S2 is 50 mg and the cyclohexane is 240 μL.

[0064] Other conditions and steps refer to Example 1.

[0065] Example 3 Preparation of a tumor microenvironment responsive mesoporous polydopamine nanodiagnostic agent

[0066] The difference between Example 3 and Example 1 is that the reaction time in step S1 is 12 hours; and the reaction time in step S2 is 8 hours.

[0067] Other conditions and steps refer to Example 1.

[0068] Comparative Example 1 Preparation of a tumor microenvironment responsive mesoporous polydopamine nanodiagnostic agent

[0069] The difference between Comparative Example 1 and Example 1 is that in step S2, 1,3,5-trimethylbenzene (TMB) and block copolymer F127 are used as templates instead of cyclohexane and P-123.

[0070] Other conditions and steps refer to Example 1.

[0071] Comparative Example 2 Preparation of a tumor microenvironment responsive mesoporous polydopamine nanodiagnostic agent

[0072] The difference between Comparative Example 2 and Example 1 is that the pH is not adjusted in step S1, so that dopamine is polymerized in advance.

[0073] Other conditions and steps refer to Example 1.

[0074] Experimental Example 1 Morphology Characterization

[0075] 1. Experimental methods

[0076] 10 μL of the CMs and CMMs sample solutions prepared in Example 1 and the CMs prepared in Comparative Examples 1 to 2 were respectively added dropwise to the front of the carbon support film and placed in a dryer to dry naturally at room temperature. The microscopic morphology (morphology, particle size and dispersion) of the CMs and CMMs was observed using a transmission electron microscope under a voltage of 120 KV.

[0077] 2. Experimental results

[0078] Depend on Figures 2-3 It can be seen that when using 1,3,5-trimethylbenzene (TMB) and block copolymer F127 as templates, the process of preparing copper-doped mesoporous polydopamine is prone to large aggregates or pore size disappearance ( Figure 2 ); In addition, when dopamine hydrochloride is mixed with metal ions, it is very easy to cause premature polymerization of dopamine, which greatly affects the morphology of the subsequently synthesized mesoporous polydopamine. Even if P-123 and cyclohexane are used as templates, polydopamine aggregates without mesoporous morphology will still be produced ( Figure 3 ).

[0079] The present invention adjusts the process to avoid premature polymerization of dopamine hydrochloride after mixing with copper ions, and simultaneously screens different surfactants and polar molecules, and finds that the CMs (such as Figure 4 A in Figure ) and CMMs (as shown in Figure ). Figure 4 The spherical structures (as shown in B) are uniform in size and complete in structure, and all of them are spherical structures with mesopores, which alleviates the problems of large aggregates or disappearance of pore size that are easily generated in the traditional preparation process.

[0080] Experimental Example 2 Particle size and potential characterization

[0081] 1. Experimental methods

[0082] 1 mL of the CMs and CMMs sample aqueous solutions prepared in Example 1 were added to the particle size dish and the potential dish, respectively, and the particle size (Average Size), polydispersity index (PDI) and Zeta potential (Zeta Potential) of CMs and CMMs were measured using a Malvern particle size analyzer.

[0083] 2. Experimental results

[0084] The results are as follows Figure 5As shown in Table 1, CMs and CMMs have good dispersibility, with similar Zeta potentials of -15.21mV and -19.83mV respectively, which can effectively escape the capture of proteins in the blood, thereby prolonging the circulation time. After coating the 4T1 cell membrane, the particle size of CMMs increased slightly from 285.9nm to 319.2nm. The measurement results of transmission electron microscopy and dynamic light scattering (DLS) are different because the latter obtains the particle size of nanoparticles in a hydrated state, and the solvent effect makes the nanoparticles show a larger hydrated particle size.

[0085] Table 1 Dispersibility, particle size and Zeta potential of CMs and CMMs nanoparticles

[0086]

[0087] In addition, the experimental results of Examples 2 to 3 are substantially the same as those of Example 1 and will not be described in detail herein.

[0088] Experimental Example 3: X-ray Photoelectron Spectroscopy Analysis

[0089] 1. Experimental methods

[0090] Take an appropriate amount of the CMMs sample prepared in Example 1, freeze-dry it and evenly spread it on an aluminum foil with double-sided tape (about 2 mm×2 mm), flatten it with a tablet press, and use an X-ray photoelectron spectrometer (Nexsa, Thermo Fisher) to determine the content and valence of the Cu element in the sample.

[0091] 2. Experimental results

[0092] The results are as follows Figure 6 As shown in Figure 2, the full scan spectrum of CMMs shows that it has characteristic peaks at 285, 400, 531 and 933 eV, corresponding to orbitals C1s, N 1s, O 1s and Cu 2p, respectively, further confirming the presence of C, N, O and Cu elements. The characteristic peaks at 933 eV and 935 eV correspond to Cu 2+ Cu 2p orbitals, demonstrating that Cu 2+ existence.

[0093] In addition, the experimental results of Examples 2 to 3 are substantially the same as those of Example 1 and will not be described in detail herein.

[0094] Experimental Example 4 Inductively Coupled Plasma-Atomic Emission Spectrometry Elemental Analysis

[0095] 1. Experimental methods

[0096] Take an appropriate amount of the CMMs solution prepared in Example 1, add an appropriate amount of concentrated nitric acid, slowly heat to 130°C in an oil bath and nitrate for 48 hours until the solution becomes colorless, transparent and free of precipitation. Dilute and filter the nitrated solution with deionized water and finally set the volume to 10 mL. Inductively coupled plasma-atomic emission spectroscopy (ICP-OES) was used to determine the Cu content in CMMs.

[0097] 2. Experimental results

[0098] Results The content of Cu in CMMs was measured by ICP-OES and was 8.13 wt%.

[0099] In addition, the experimental results of Examples 2 to 3 are substantially the same as those of Example 1 and will not be described in detail herein.

[0100] Experimental Example 5: Study on photothermal properties in vitro

[0101] 1. Experimental methods

[0102] The CMMs prepared according to the method of Example 1 were configured into CMMs aqueous solutions of different concentrations, placed in a 2 mL cuvette, and irradiated with 808 nm near-infrared laser to characterize the heating curve, photothermal stability and photothermal conversion efficiency of the CMMs.

[0103] 2. Experimental results

[0104] The results are as follows Figure 7 As shown in the figure, the CMMs material exhibits a temperature change that depends on the concentration and laser power. This result shows that CMMs has good photothermal conversion ability and can effectively convert near-infrared light energy into thermal energy. The temperature change (ΔT) of the CMMs solution in the four heating and cooling cycles is not much different, indicating that CMMs has good photothermal stability. The photothermal conversion efficiency (η) of CMMs was then calculated. It was calculated by formula (1) that it has a high photothermal conversion rate, and the η value is 34.19%.

[0105]

[0106] In addition, the experimental results of Examples 2 to 3 are substantially the same as those of Example 1 and will not be described in detail herein.

[0107] Experimental Example 6 In vitro magnetic resonance imaging study

[0108] 1. Experimental methods

[0109] CMMs (CMMs prepared in Example 1) under different conditions were measured using 3.0T and 7.0T magnetic resonance imaging devices, respectively, to characterize their T1 and T2 weighted MRI imaging effects and calculate relaxation. The present invention creatively uses copper ions for MRI imaging, and achieves T1-T2 dual-modality MRI-guided tumor treatment through a simple method. CMMs home to the tumor area, and through the changes in MRI signals responsive to glutathione (GSH) and H2O2, accurate diagnosis of tumors is achieved. At the same time, the Fenton-like reaction of copper is detected by MRI signals to monitor the process of tumor chemokine therapy.

[0110] 2. Experimental results

[0111] Compared with the solid metal-doped polydopamine, the copper-doped mesoporous polydopamine obtained by the present invention has a rich mesoporous structure, and its mesoporous structure increases the specific surface area. The larger specific surface area not only accelerates the + The mediated Fenton reaction rate will also enhance the interaction between copper ions and surrounding water protons, which is beneficial to improving MRI effects. Figure 8 , Fig. 9 As shown, with Cu 2+ As the concentration increases, the T1 image gradually becomes brighter and the T2 image gradually becomes darker, that is, the contrast effect gradually increases. The calculation found that the r1 and r2 values ​​of CMMs at a field strength of 3.0T are 9.53mM and 9.62mM, respectively. -1 s -1 and 6.81mM -1 s -1 ( Figure 8 B); while under CMMs+GSH+H2O2 conditions, the r1 and r2 values ​​were 1.99 mM -1 s -1 and 1.69mM -1 s -1 ( Figure 8 C in the figure). The r1 and r2 values ​​of CMMs at 7.0T are 1.285mM respectively. -1 s -1 ( Fig. 9 B) and 22.874mM -1 s -1 ( Fig. 9 C); after adding GSH, the r1 and r2 values ​​were 0.977mM -1 s -1 and 16.396mM -1 s -1 ; After further addition of H2O2, the r1 and r2 values ​​were 1.017mM -1 s -1 and 20.572mM -1 s-1 After adding GSH and H2O2, the relaxation rate of CMMs decreased significantly. This is because after adding GSH and H2O2, Cu 2+ It will react with GSH to form Cu + and GSSG lead to Cu for MRI imaging 2+ The above results show that the CMMs obtained by the present invention have excellent T1-T2 dual-mode magnetic resonance imaging capabilities. At the same time, the Fenton-like reaction of copper can be detected by MRI signals to accurately monitor the process of tumor chemokinetic therapy.

[0112] In addition, the experimental results of Examples 2 to 3 are substantially the same as those of Example 1 and will not be described in detail herein.

[0113] Experimental Example 7 In vitro chemical kinetics study

[0114] 1. Experimental methods

[0115] MB is a typical ·OH reaction reagent. When ·OH is present, MB will fade, and can be quantitatively analyzed based on the change in the absorbance value of the MB characteristic peak at 664nm. After the CMMs prepared according to the method of Example 1 were incubated for different time periods under different treatment conditions, the absorbance value of each group of samples at 664nm was detected on a UV-visible spectrophotometer.

[0116] 2. Experimental results

[0117] The results are as follows Fig.10 As shown in A, the absorbance at 664 nm decreased significantly in the group with H2O2, CMMs, MB and GSH at pH 6.5. In the experimental group with pH 5.0, the absorbance at 664 nm decreased further. This is because the Cu 2+ Reacts with GSH to generate Cu + and GSSG, Cu + Further, H2O2 is catalyzed to generate ·OH through a Fenton-like reaction, which increases the generation of ·OH in an acidic environment. Fig.10 As shown in Figure B, the absorbance value at 664nm in a solution with a pH of 5.0 after adding H2O2, CMMs, MB and GSH shows a relationship with time, indicating that the nano-diagnostic agent CMMs can achieve a Fenton-like continuous catalytic reaction. The above results prove that CMMs have good Fenton-like catalytic properties and can be used for chemokinetic therapy. It also shows that the obtained nano-diagnostic agent CMMs can effectively respond to the acidic conditions of the tumor microenvironment and can achieve Cu in the tumor microenvironment. 2+ / Cu + Efficient conversion, efficient production of ·OH, inducing tumor cell death.

[0118] In addition, the experimental results of Examples 2 to 3 are substantially the same as those of Example 1 and will not be described in detail herein.

[0119] Experimental Example 8 In vitro biocompatibility study

[0120] 1. Experimental methods

[0121] The effect of CMMs prepared according to the method of Example 1 on the viability of HUVEC cells (human umbilical vein endothelial cells) was investigated by MTT colorimetry. The absorbance value A at 570 nm was detected by an ELISA instrument. The cell survival rate was calculated according to formula (2):

[0122]

[0123] 2. Experimental results

[0124] like Fig.11 As shown in the figure, as the sample concentration increases, the cell survival rate of HUVEC remains basically unchanged, close to 100%. When the CMMs concentration is as high as 200 μg / mL, the cell survival rate of HUVEC is still over 80% after 48 hours of co-incubation, indicating that CMMs have good biocompatibility.

[0125] In addition, the experimental results of Examples 2 to 3 are substantially the same as those of Example 1 and will not be described in detail herein.

[0126] Experimental Example 9 In vitro cytotoxicity study

[0127] 1. Experimental methods

[0128] The effect of CMMs on 4T1 cell viability was investigated by MTT colorimetry. The absorbance A at 570 nm was detected by an ELISA instrument. The cell viability was calculated according to formula (2).

[0129] 2. Experimental results

[0130] like Fig.12As shown, after 4T1 cells were co-incubated with CMs and CMMs, the cell survival rate showed a decrease in dependence on the concentration of CMs and CMMs. In contrast, when treated with laser irradiation (such as CMMs+L), the cell survival rate decreased faster. In particular, when the concentration of CMMs was 200μg / mL, the cell survival rates were 58.9% and 32.6% without or with laser treatment, respectively, which proves the superiority of CMMs in photothermal and chemodynamic combined therapy. As can be seen from the figure, CMMs have basically the same effect as CMs in photothermal and chemodynamic combined therapy. This is because CMMs are formed by the adsorption of tumor cell membranes on the surface of CMs. Since the cell membrane does not change the molecular structure of CMs, CMMs perfectly inherit the physical properties of CMs. Therefore, in other properties such as magnetic resonance imaging, the effects of CMs and CMMs are basically the same.

[0131] In addition, the experimental results of Examples 2 to 3 are substantially the same as those of Example 1 and will not be described in detail herein.

[0132] Experimental Example 10 Study on the specific recognition of tumors by homologous targeting ability

[0133] 1. Experimental methods

[0134] The homologous targeting ability of CMMs to tumors was investigated by MTT colorimetry. The absorbance value A at 570 nm was detected by an ELISA instrument. The cell survival rate was calculated according to formula (2).

[0135] 2. Experimental results

[0136] like Fig.13 As shown in the figure, 4T1 cells (mouse breast cancer cells) and Hepa1-6 cells (mouse liver cancer cells) were co-incubated with CMMs, respectively, and the cell survival rate showed a decrease in dependence on the CMMs concentration. In addition, the survival rates of different cells were different. After 24 hours of co-incubation with cells at the highest concentration, the survival rate of 4T1 cells was only 32.6%, which was significantly lower than the survival rate of Hepa1-6 cells under the same conditions, further proving that the 4T1 cell membrane in CMMs has good homologous targeting ability.

[0137] In addition, the experimental results of Examples 2 to 3 are substantially the same as those of Example 1 and will not be described in detail herein.

[0138] In summary, the present invention uses dopamine hydrochloride and copper salt as basic raw materials, and P-123 and cyclohexane as templates to prepare copper-doped mesoporous polydopamine Cu-MPDA (CMs), and further wraps the mouse breast cancer cell (4T1 cell) membrane on its surface to prepare multifunctional nano-diagnostic agent CMMs, which is used for ultra-high field T1-T2 magnetic resonance imaging-guided photothermal-chemodynamic combined treatment of cancer. Specifically, the in vitro MRI imaging results show that the nano-diagnostic agent CMMs has ultra-high field T1-T2 dual-mode magnetic resonance imaging capabilities, can effectively monitor the process of tumor chemodynamic therapy through MRI signals, and the nano-diagnostic agent CMMs can specifically identify tumors through the homologous targeting ability of 4T1 cell membranes, and can achieve Cu in the tumor microenvironment. 2+ / Cu + It can efficiently convert GSH and produce a large amount of ·OH. It shows good photothermal conversion ability under near-infrared light (NIR) irradiation, and can realize the combined cancer treatment of photothermal-promoted chemokinetics. In addition, since CMMs are formed by the adsorption of tumor cell membranes on the surface of CMs, the homing effect of tumor cell membranes gives CMMs the ability to actively target. At the same time, since the cell membrane does not change the molecular structure of CMs, CMMs perfectly inherit the physical properties of CMs. Therefore, in terms of XPS spectra, photothermal properties, magnetic resonance imaging properties, and chemokinetic reaction capabilities, the effects of CMs and CMMs are basically the same.

[0139] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing copper-doped mesoporous polydopamine nanoparticles, characterized in that: The steps include: S1. Add dopamine hydrochloride to a mixed solution of ethanol and water, add a copper salt solution, adjust the pH of the solution to 4-5, continue stirring in the dark, and react completely to obtain a copper chelated dopamine solution; S2, adding P-123 and cyclohexane to the copper-chelated dopamine solution obtained in step S1, adjusting the pH of the solution to 9-11 after sufficient dispersion, continuously stirring in the dark, fully reacting, and post-treating to obtain copper-doped mesoporous polydopamine nanoparticles; Wherein, the mixing ratio of dopamine hydrochloride, P-123 and cyclohexane is 1 mg: (3-5) mg: (16-24) μL; The copper salt is selected from one or more of copper sulfate, copper chloride and copper nitrate; The mass ratio of the copper salt to dopamine hydrochloride is 1:(10-12).

2. A copper-doped mesoporous polydopamine nanoparticle, characterized in that: The method is prepared according to claim 1.

3. The copper-doped mesoporous polydopamine nanoparticles according to claim 2, characterized in that: The copper doping amount in the copper-doped mesoporous polydopamine nanoparticles is 8-10 wt %.

4. A multifunctional mesoporous polydopamine-based nano-diagnostic agent, characterized in that: The invention comprises the copper-doped mesoporous polydopamine nanoparticles as claimed in claim 2 or 3 and a tumor cell membrane wrapped on the surface of the mesoporous polydopamine nanoparticles.

5. The multifunctional mesoporous polydopamine-based nano-diagnostic agent according to claim 4, characterized in that: The tumor cell membrane is selected from one or more of breast cancer cell membrane, cervical cancer cell membrane and liver cancer cell membrane.

6. The multifunctional mesoporous polydopamine-based nano-diagnostic agent according to claim 5, characterized in that: The breast cancer cell membrane is a 4T1 cell membrane, an MDA-MB-231 cell membrane or an MCF-7 cell membrane.

7. The method for preparing the multifunctional mesoporous polydopamine-based nano-diagnostic and therapeutic agent according to any one of claims 4 to 6, characterized in that: The method comprises the following steps: fully mixing the tumor cell membrane with the copper-doped mesoporous polydopamine nanoparticles, and then repeatedly extruding the copper-doped mesoporous polydopamine nanoparticles and the tumor cell membrane to obtain the obtained product.

8. Use of the copper-doped mesoporous polydopamine nanoparticles according to claim 2 or 3 or the multifunctional mesoporous polydopamine-based nano-diagnostic and therapeutic agent according to any one of claims 4 to 6 in any one or more combinations of preparing magnetic resonance imaging contrast agents, preparing tumor photothermal therapeutic agents, and preparing tumor chemodynamic therapeutic agents.

Citation Information

Patent Citations

  • Multifunctional composite nano-enzyme material for collaborative treatment of tumors as well as preparation method and application of multifunctional composite nano-enzyme material

    CN115944728A

  • Magnetic mesoporous polydopamine composite material with core-shell structure as well as preparation method and application of magnetic mesoporous polydopamine composite material

    CN112275263A

  • Mesoporous polydopamine nanoparticles for tumor T1-T2 magnetic resonance imaging

    CN112759762A

  • Glutathione response type nano hydrogel coated with cell membrane and preparation method of glutathione response type nano hydrogel

    CN116098857A